2012
DOI: 10.1002/yea.2924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature upon vitality of Saccharomyces cerevisiae phospholipid mutants

Abstract: The phospholipid metabolism of Saccharomyces cerevisiae plays a central role in its adaptation to low temperatures. In order to detect the key genes in this adaptation, various phospholipid mutants from the EUROSCARF collection of Saccharomyces cerevisiae BY4742 were tested to ascertain whether the suppression of some genes could improve the fermentation vitality of the cells at low temperature. The cell vitality and phospholipid composition of these mutants were analysed. Some knockouts improved (hmn1Δ) or im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…S3). These results were consistent with the expected changes on lipid composition upon a shift of temperature, as this particular pathway has been already related to acclimatization to temperature , and its disruption results in a poor performance at suboptimal temperatures . Other metabolites affected by the temperature and identified were also related to lipid metabolism, like LysoPE(14:1(9Z)/0:0) or leukotriene B4 (Table ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S3). These results were consistent with the expected changes on lipid composition upon a shift of temperature, as this particular pathway has been already related to acclimatization to temperature , and its disruption results in a poor performance at suboptimal temperatures . Other metabolites affected by the temperature and identified were also related to lipid metabolism, like LysoPE(14:1(9Z)/0:0) or leukotriene B4 (Table ).…”
Section: Resultssupporting
confidence: 86%
“…Whereas transcriptomic analyses usually failed to detect any temperature‐related effect on lipid metabolism, metabolomic studies consistently showed changes in lipid and phospholipid metabolism . Changes in lipid composition have been genetically identified as crucial on the acclimatization of the yeast cells to temperature changes . It is likely than other metabolic changes equally important for yeast growth could have been overlooked by transcriptomic or other mRNA quantitation‐based analyses, whereas they can be adequately described by metabolomic studies.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have overexpressed the gene encoding the S. cerevisiae desaturase OLE1 (Kajiwara et al, 2000) or other heterologous desaturases (Rodríguez-Vargas et al, 2006) in order to increase the degree of unsaturation and membrane fluidity, while improving the cold resistance of these engineered strains. In a recent work (Redón et al, 2012), we have also detected an improved or impaired fermentation vitality in some mutants of the phospholipid biosynthesis. In the present study, we have screened most of the mutants of the laboratory strain BY4742 encoding enzymes of the phospholipid, sterol and sphingolipid pathways in terms of their growth capacity at low temperature.…”
Section: Discussionmentioning
confidence: 69%
“…In this respect, knock-out or overexpression of genes related with lipid metabolism can modify the architecture of this plasma membrane. In a preliminary study (Redón et al, 2012), we tested various phospholipid mutants from the EUROSCARF collection of S. cerevisiae BY4742 to ascertain whether the suppression of some genes could improve the fermentation vitality of the cells at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of this pathway has a widespread influence on other cellular pathways, some of which have a huge potential impact on adaptation at low temperature, such as in the phospholipid (PL) biosynthesis pathway. Changes in the phospholipid composition of cellular membranes as a response to low temperature have been widely reported [ 28 , 29 , 36 , 37 ]. Phosphatidylcholine (PC), the major phospholipid (at least 30% of total PLs), is synthesized de novo from another PL, phosphatidylethanolamine (PE), in three SAM-consuming methyltransferase reactions catalyzed by Opi3p and Cho2p [ 38 ].…”
Section: Discussionmentioning
confidence: 99%